Selecting Appropriate Cotton Based Cropping Pattern for Increasing Cropping Intensity in Bangladesh - Kundu, S; Hassan, K; Alam, SMJB; Uddin, MF (Journal of Environmental Science and Natural Resources, 2019)
The experiment was conducted at Cotton Research, Training and Seed Multiplication Farm, Jagodishpur, Chowgacha, Jessore initiated June 19, 2015 for the cropping season 2015-16 to observe the performance of cotton based cropping system including total three crops in a year. The other crops were i) relay wheat – mungbean and ii) relay lentil – mungbean. Four cotton varieties CB-12, CB-13, CB-14 and CB Hybrid-1 were sowed in a RCBD design with three replications. Seed cotton yield was significantly different among the varieties. The highest seed cotton yield (2519.3 kg/ha) was obtained from CB Hybrid-1 and the lowest (2112.37 kg/ha) seed cotton was produced by CB-13. The highest BCR (1.31) was observed in cotton (CB Hybrid-1) –relay lentil –mungbean cropping pattern and the lowest BCR (1.10) was observed in Cotton (CB-13) – relay wheat –mungbean cropping pattern. The finding infers that cotton – relay lentil - mungbean cropping pattern might have the potentiality to increase cropping intensity in Bangladesh. J. Environ. Sci. & Natural Resources, 11(1-2): 37-41 2018